PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP PELAYANAN PUBLIK DI DESA BANUA KECAMATAN BUNGIN KEBUPATEN ENREKANG - Rosnani; Tajuddin, Sapri; Hardianti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The aim of the research is to determine the application of good governance principles to public services in Banua village, Bungin sub-district, Enrekang district, to determine supporting and inhibiting factors in the application of good governance principles to public services in Banua village, Bungin sub-district, Enrekang district. The population of this study was 194 heads of families in Banua village. The sample in this research was 66 heads of families, taken based on non-probability sampling techniques. The type of this research is quantitative descriptive. Data collection techniques used were observation, interviews, literature study and questionnaires. The data analysis technique used is validity, reliability and simple linear regression using the help of the IBM SPSS Statistics 21.0 application. The research results show that the implementation of Good Governance principles in Banua village is in the "good" category with results of 80%. Public services in Banua Village are in the "Good" category with a percentage result of 63%. The application of the principles of Good Governance to Public Services in Banua Village, Bungin District, Enrekang Regency is in the category with the "significant/influential" level, from the ANOVA test, the F count obtained is 19,725 with a significant level of 0.003, based on the t value > t table. or 3,012 ≥ 1.667 then H0 is rejected, meaning that the level of implementation of Good Governance Principles is significant/influences public services in Banua Village, Bungin District, Enrekang Regency.